2018
DOI: 10.1021/acsami.7b18277
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Cancer HeLa Cell Autocrine Apoptosis Induced by Coimmobilized IFN-γ plus TNF-α Biomaterials

Abstract: Using external methods to induce the death of cancer cells is recognized as one of the main strategies for cancer treatment. Research indicated that TNF-α is frequently used in tumor biotherapy while IFN-γ can directly inhibit tumor cell proliferation. In our study, TNF-α and IFN-γ were coimmobilized on polystyrene material (PSt) or FeO-oleic acid nanoparticles (NPs). Then the structural change of these two proteins can be observed. Meanwhile, the expressions of both TNF-α and IFN-α increased significantly, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Studies showed that the proliferation and activation of host T cells was suppressed by IFN-γ indirectly, which protected mice against GVHD [62,93,94]. Moreover, IFN-γ was proven to have a positive therapeutic effect on human malignancies [95][96][97], and it could promote DNT cell-mediated killing of leukemia cells by facilitating NKG2D and DNAM-1 ligand expression [36]. Furthermore, IFN-γ increased Fas and FasL protein expression to inhibit leukemia K562 cell proliferation and promote cell apoptosis [98].…”
Section: Cytokinesmentioning
confidence: 99%
“…Studies showed that the proliferation and activation of host T cells was suppressed by IFN-γ indirectly, which protected mice against GVHD [62,93,94]. Moreover, IFN-γ was proven to have a positive therapeutic effect on human malignancies [95][96][97], and it could promote DNT cell-mediated killing of leukemia cells by facilitating NKG2D and DNAM-1 ligand expression [36]. Furthermore, IFN-γ increased Fas and FasL protein expression to inhibit leukemia K562 cell proliferation and promote cell apoptosis [98].…”
Section: Cytokinesmentioning
confidence: 99%
“…As a proinflammatory cytokine, TNFα had been reported to be associated with cell proliferation, differentiation, apoptosis, and immune response. Moreover, Li et al indicated that TNF-α induced the apoptosis of cervical cells ( Li J. et al, 2018 ). Rashmi et al suggested that AKT inhibitors suppress the proliferation of cervical cancer cells via disruption of mTOR signaling and glucose uptake ( Rashmi et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…All these experiments above confirmed that the EVO has powerful anti-cancer effects against gallbladder cancer. P38 MAPK pathway regulates various cellular activities concerned with cancer development, including proliferation, differentiation, apoptosis and inflammation [27,28] Tumor necrosis factor-α(TNF-α), which is major mediator of extrinsic apoptosis, was initially considered only to be secreted by inflammation-related cells such as macrophages, but more recent research has found that a wide variety of tumor cells can secrete TNF-α, including breast, ovarian, colon cancers [29]. P38 MAPK pathway can be activated by various types of cellular stress such as oxidative, genotoxic, and osmotic stress and maybe more importantly by pro-inflammatory cytokines such as TNF-α [27].…”
Section: Discussionmentioning
confidence: 99%